Rekonstruksi Marjinalisasi Kaum Perempuan Pada Tradisi Khatam Qur’an - Momy A Hunowu; Hatim Badu Pakuna; Muhammad Obie (Al-Ulum, 2023)
The focus of this paper is to explore how the tradition of khatam Qur’an for women is the entry point for empowerment. The research was conducted using a qualitative approach, collecting data through in-depth interviews with four female research participants and observing their family life. The results of the research show that the tradition of khatam Qur'an has opened up opportunities for women’s freedom. In the first generation, women were still cooped up, illiterate and shy, in the second generation, opportunities for freedom were given with the excuse of leaving the house to learn the Qur’an reading. In the third generation, women are equal to men in education to obtain public roles. However, they cannot let go of their domestic role. In the end, women have a dual role. This study concludes that ongoing empowerment efforts have reconstructed the marginalization of women.